PENETRATING EYELID INJURY DUE TO FISHING HOOK : AN UNUSUAL CASE: Poster Presentation - Case Report - Resident - BIMA RYANDRA PUTRA; RIANI ERNA (Majalah Oftalmologi Indonesia, 2023)
Introduction : Ocular penetrating injury due to fishing hook is rarely reported. Identifying organ structures involved and determining appropriate approach will affect the outcome. This special case explained penetrating eyelid injury due to fishing hook without ocular involvement. Case Illustration : R, boy, 12y.o, came to M.Hoesin ED in January 2023 with complaint of left eye was exposed to fishing hook one hour before admission. Patient was experiencing mild pain with pain scale of three, no blurry vision, excessive tears nor blood. History of immunization was uncomplete.There was no significant visual disturbance. On left superior palpebra, there was a fishing hook penetrated into the medial superior palpebra (partial thickness) without any marginal involvement, no active bleeding, and corneal abrasion in central-paracentral nasal 6-9 o’clock direction. Patient was diagnosed with penetrating eyelid injury due to fishing hook. Intraoperatively back-out technique were performed to extract the fishing hook. Patient was prescribed with 250IU Tetagam injection, chloramphenicol eye ointment, and oral analgetic. Discussion : Ocular penetrating fishing hook injury could cause severe complications. In this patient, it only penetrates the eyelid until the dermis layer without marginal involvement. Complications occurred were only corneal erosion with minimal pain. After the operative procedure, topical antibiotic and analgetic were administered. There was no decreased levator palpebra function and corneal erosion was resolved in three days after topical antibiotics were administered. Conclusion : Management of ocular penetrating fishing hook injury is challenging. Determining the best technique to extract the fishing hook depends on the depth and type of fishing hook.